Evaluasi Jaringan Sistem Pipa Gua Pulejajar Menggunakan EPANET 2.2: Solusi Irigasi Berkelanjutan di Kawasan Karst Gunungkidul - Muchamad Arif Budiyanto; Ratih Nurmala Saridewi; Afnan Juli Arochma (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The karst region of Gunungkidul Regency is characterized by highly permeable limestone formations that cause rainwater to rapidly infiltrate into the ground, resulting in limited surface water availability. Pulejajar Cave, located in Jepitu Village, Girisubo District, Gunungkidul Regency, serves as an important groundwater source utilized to irrigate approximately 200 hectares of agricultural land. This study aims to evaluate the hydraulic performance of the Pulejajar Cave water distribution network and determine the optimal pipe dimensions using EPANET 2.2. The data employed in this study include the existing distribution network map, pipe dimensions and characteristics, elevation data, and irrigation water demand of 1.45 L/s/ha. Hydraulic simulations were conducted to analyze flow rate, velocity, pressure, and network optimization requirements.The results indicate that the total water supply from Pulejajar Cave reaches 2,738.98 L/s, while the total irrigation water demand is 1,031.95 L/s, resulting in a surplus of 1,707.03 L/s or 165.41% above the required demand. Despite this substantial water availability, the evaluation of the existing network revealed several pipe sections that did not satisfy the hydraulic criteria for HDPE pipes. In particular, Pipe Puncung 1 exhibited a flow velocity of 9.03 m/s, significantly exceeding the recommended maximum limit of 3.0 m/s. Through pipe dimension optimization, the diameter of Pipe Puncung 1 was increased from 90 mm to 200 mm, successfully reducing the flow velocity to 1.83 m/s, which complies with the recommended design standards. Further optimization of other critical pipe segments also improved hydraulic performance, enhanced distribution efficiency, and minimized the risk of infrastructure deterioration. Therefore, EPANET 2.2 proved to be an effective tool for evaluating and optimizing water distribution networks, supporting the sustainability of irrigation systems in the karst region of Gunungkidul